MAKNA SIMBOL UPACARA ADAT PABUAT BORU PADA MASYARAKAT BATAK MANDAILING DI KABUPATEN TAPANULI SELATAN SUMATERA UTARA - Siregar, Hamdani Al Rasyid; ", Yasir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The pabuat boru traditional ceremony is a marriage ceremony in the Mandailing Batak tribe. Until now the ceremony is still ongoing and carried out by the Mandailing Batak community in the South Tapanuli Regency of North Sumatra. This ceremony involves various various elements of society. This research is focused on the purpose of knowing how the symbols of the traditional ceremony of pabuat boru in the Mandailing Batak community in South Tapanuli Regency, North Sumatra. To answer the above problems, the sub-focus of research on symbolic interaction was raised in the traditional ceremony of pabuat boru and to know the meanings contained in the traditional ceremony of pabuat boru. This study uses qualitative research methods with a descriptive approach. The subject of this study was the informantThe results of this study are the pabuat boru ceremony, a tradition of ceremonies carried out by Mandailing Batak people in South Tapanuli District, North Sumatra. In this connection the bride departed with a traditional ceremony from her parents' house to the house of the groom's parents. This activity is what is meant by pabuat boru. At this stage the symbols that are interpreted are the gates at the wedding event, this gate is made right in front of entering the yard, usually consists of two bamboo decorated with young coconut leaves with writing horas tondi madingin sayur matua bulung. The second is traditional cloth (ulos adat). Ulos adat in Mandailing is called by the name tonun patani, which is reddish brown combined with gold thread and sirumbai. The third burangir (betel leaf) in the burangir mandailing tradition plays an important role, because the presence of burangir indicates that the work carried out is according to adat. Burangir is needed if it is going to invite customary kings or if a customary congregation is held, in the customary language of burangir called napuran. The last one which is called upa-upa is some kind of cooked food that is placed on a special container. Keywords: The Meaning Of The Symbols Of The Traditional Ceremony Of Pabuat Boru